Gender inequality in the midst of the transformation of the work role of the community around the Putri Cempo Power Plant, Jatirejo Village - Fauzan Addinul Jihad; Dwi Kurniadi; Farhat Abdillah To Ngili; Aufa Ubadah An Nu'man; Martarosa Maulidia (Privietlab, 2026)
The development of the Putri Cempo Waste Power Plant or Pembangkit Listring Tenaga Sampah (PLTSa) is often framed as a technological solution, yet it triggers complex social friction within the surrounding informal sector. Previous studies have focused heavily on environmental impacts, neglecting socio-structural dynamics. This study aims to analyze the transformation of work roles and the reconstruction of gender inequality in Jatirejo Village before and after the PLTSa construction from a structural-functional perspective. Employing a qualitative descriptive method, data were collected through in-depth interviews with key informants in May 2025. The analysis utilized Miles and Huberman’s interactive model to correlate field findings with social change theory. The study reveals an irony of development mapped into two phases: First, the Invention Phase, where the community shifted from an agrarian to a waste-based subsistence economy not as innovation, but as a survival mechanism. Second, the Diffusion Phase, where PLTSa technology acted as an instrument of exclusion, severing access to economic resources, occurred. A critical finding is the radical reconstruction of gender roles: men experienced structural paralysis due to formal employment co-optation, creating a political agency void. Consequently, women have transformed from domestic roles into the vanguard of environmental advocacy to fill this void. Community resilience in Jatirejo is not a product of development but a self-balancing mechanism achieved at the cost of women's double burden as both domestic caretakers and the last bastion of community defense.